2013
DOI: 10.1007/s10750-013-1675-6
|View full text |Cite
|
Sign up to set email alerts
|

Muddied waters: suspended sediment impacts on gill structure and aerobic scope in an endangered native and an invasive freshwater crayfish

Abstract: Suspended sediment (SS) loadings in freshwater habitats have increased over the past century and SS is now a significant environmental stressor. Greater tolerance to environmental stressors has been proposed as a factor in the success of aquatic invasive species. Further, parasites may interact with environmental stressors to increase host susceptibility to loss of fitness and mortality. We compared the effects of SS exposure on the gill structure and aerobic scope of the endangered white-clawed crayfish (Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 83 publications
2
39
0
1
Order By: Relevance
“…However, alterations to suspended sediment concentrations as demonstrated here may facilitate further advantages over native species because Rosewarne et al . [] have shown that A. pallipes are significantly less tolerant of suspended sediment than signals, suffering greater gill fouling, gill damage, and reduced aerobic scope across a range of sediment concentrations. Therefore, the ecosystem engineering activities of P. leniusculus may have contributed to their invasive success.…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations to suspended sediment concentrations as demonstrated here may facilitate further advantages over native species because Rosewarne et al . [] have shown that A. pallipes are significantly less tolerant of suspended sediment than signals, suffering greater gill fouling, gill damage, and reduced aerobic scope across a range of sediment concentrations. Therefore, the ecosystem engineering activities of P. leniusculus may have contributed to their invasive success.…”
Section: Discussionmentioning
confidence: 99%
“…If crayfish rather than fish are tested, a two‐stage exhaustion protocol is adopted (Rosewarne et al , ). Individual crayfish are placed in a shallow tray (40 cm × 25 cm × 4 cm) of water at the experimental temperature and induced to tail flip by repeatedly touching the tail fan (telson) with the blunt end of a pencil.…”
Section: Methodsmentioning
confidence: 99%
“…The unit for oxygen consumption rate in equation (3) is mg O 2 kg −1 h −1 (Steffensen et al , ). A value of A = 0·8 is commonly used for fishes (Holeton, ; Skov et al , ) and A = 0·71 for crayfish (McFeeters et al , ; Rosewarne et al , ), although species‐specific values should be used when available [see Table SII (Supporting Information) for sample calculations].…”
Section: Methodsmentioning
confidence: 99%
“…No information exists regarding the long term status of this population, and this level of TSS may be a result of habitat degradation. A laboratory study by Rosewarne et al (2014) found that levels above 500 mg·L −1 resulted in gill fouling in all exposed crayfish (A. pallipes), whilst 250 mg·L −1 was associated with fouling in 92% of exposed individuals. However, the same study did not find any reduction in survival over 45 days in concentrations up to 1000 mg·L −1 , indicative of at least short-term tolerance for extremely high levels.…”
Section: > Total Suspended Solids (Tss) and Siltationmentioning
confidence: 99%